Syntax in reddit comments: An analysis of responses on coping with life’s lowest points - Marilou D. Licup; Richel R. Ramos; Rodolfo P. Dizon Jr. (Yayasan Mitra Persada Nusantara, 2026)
Syntax, or the arrangement of words and phrases into sentences, plays a crucial role in shaping meaning. In digital communication, informal and rapid exchanges have led to noticeable shifts in sentence structures, particularly in online communities such as Reddit, where users share personal experiences and seek support. This study analysed ten comments from the r/INTJ thread “How do you cope when you’re at your lowest point in life?” to classify sentences by type and identify non-standard forms, exploring how syntax functions in casual online coping discourse. Using purposive sampling, each comment was analysed for sentence types and non-standard forms using frameworks from Quirk et al. (1985) and Crystal (2001), while all identifying information was removed to ensure ethical handling of online data. Results showed that declarative and imperative sentences were most common, reflecting users’ tendencies to share experiences and offer advice. Non-standard forms, including punctuation variation, abbreviations, informal lexical choices, and non-standard spelling, also appeared frequently. These patterns suggest that users prioritize emotional expression and support rather than strict grammatical accuracy. Based on these findings, future research may expand the corpus, compare comments across different years, and integrate semantic analysis to better understand how users construct empathy and shared meaning in online coping communities.